A review of the practice of diagnosis and management of gastroenteritis in children below 5 years in two district general hospitals. (29th September 2015) - Kunnath, MS; Chandraratne, S; Jayatunga, R
Abstract : Background: It is estimated that around 150 000 children less than 5 years present to healthcare services with symptoms of gastroenteritis each year. In 2007/08, approximately 37 000 children less than 5 years with D&V were admitted in England. In April 2009, the National Institute for Health and Clinical Excellence (NICE) introduced new guideline aiming to reduce the variation in practice and make best use of NHS resources. Key recommendations include avoidance of unnecessary stool test and rationalisation of fluid management. Clear criteria were set out for the assessment of dehydration based of red flag signs. Full strength milk is advocated during correction of dehydration and after. Use of fruit juice is discouraged. Isotonic saline with glucose is recommended for intravenous rehydration and maintenance. Aim: To review the local practice of diagnosis, investigation and management of acute gastro-enteritis in children below 5 years against new NICE guidance. Materials and Methods: A total of 75 case notes were reviewed. All of them were admitted in two nearby district general hospital. 23% of them had clinical dehydration. 19% received IV fluids of which 50% did not have clinical dehydration. 35% had stool culture done, of which 50% had recommended reason to test the stool. 51% of patients had some blood test done, mostly blood sugar, followed by urea and electrolytes. Only minority of the case notes had recorded flagged sings of dehydration. 76% of the patients received ORS and 63.5% were managed with ORS alone. Conclusion: Intravenous fluid usage generally was not very high. None of the children were treated with antibiotics or antidiarrhoeals. Use of ORS was encouraging. Majority of children admitted were not dehydrated and possibly could have been managed at home. Some of the stool cultures done were unnecessary. Many children had variety of blood tests, possibly unnecessary. Documentation needed to be improved, especially regarding red flag signs. None of the patients treated with intravenous fluids received isotonic saline. Many children had milk feed delayed following correction of dehydration. Only a few patients/parents were given prevention of diarrhoea advice.